Association of Rush Pin and Intramedular Pin Techniques for the Stabilization of Salter Harris Type I Fracture in Rabbit (Oryctolagus cuniculus) - Kitamura Kawamoto, Fernando Yoiti [UNESP]; Perles, Livia [UNESP]; Santos, Levi Oliveira dos [UNESP]; Simionato, Giulia Carneiro [UNESP]; Gosuen Goncalves Dias, Luis Gustavo [UNESP]; Minto, Bruno Watanabe [UNESP]; Werther, Karin [UNESP] (Univ Fed Rio Grande Do Sul, 2018)
Background: In domestic rabbits, fractures are usually the result of household accidents. Fractures of the distal femoral physis are frequently observed in animals with immature skeletons and may cause future orthopedic problems. With this type of fracture, early reduction and stabilization are necessary to prevent additional damage to the physis and to preserve the growth potential of the bone. This report aims to describe the clinical and radiographic findings, as well as the surgical method used that combined Rush pins with an intramedullary pin, associated with a Salter Harris type I fracture of the right distal femur in a rabbit. Case: A 4-month male domestic rabbit (Oryctolagus cuniculus) weighing 1.2 kg, was referred to the Veterinary Hospital with a right pelvic limb lameness after an episode of trauma. Orthopedic examination revealed swelling, instability, crepitation, and increased pain sensitivity in the distal aspect of the right femur. Following physical and radiographic examination, a Salter Harris type I fracture of the right distal femur was diagnosed. The patient was premedicated with a combination of xylazine (2 mg/kg IM) and ketamine (10 mg/kg IM), which allowed placement of an IV catheter for the administration of fluids and intubation using an endotracheal tube with an internal diameter of 2 mm. Anesthesia was maintained with isoflurane, and an epidural was performed with a combination of lidocaine (2 mg/kg) and bupivacaine (0.75 mg/kg). Osteosynthesis was performed with two Rush pins and an intramedullary pin. Radiographic examination 110 and 330 days after the surgical procedure showed good alignment of the bone and adequate healing of the fracture. The combination of techniques used in this case report proved to be effective, resulting in functional recovery of the limb and rapid bone healing. Discussion: Preoperative planning for orthopedic surgery in rabbits is different from that of dogs and cats, due to the particularities of the species. Familiarity with the regional anatomy, patient preparation, and appropriate instrumentation are necessary when contemplating osteosynthesis in a rabbit. Salter Harris fractures affect young animals, where the physis is considered an area of fragility in the bone. Surgical planning should take into account the function of the growth plates. It is recommended that implants passing through the physis do so perpendicularly, since angulation greater than 45 degrees may predispose the bone to premature closure of the growth plate. Another important consideration involves the choice of implants, since the use of trocar-tipped pins facilitates their precise placement in the bone. The use of threaded pins should be avoided due to their weakness at the thread-shaft interface, and the risk of impaired longitudinal bone growth and the difficulty of removal if necessary. Steinman pins and Kirschner wires can be used to stabilize a variety of different fractures. In Salter-Harris type I and II fractures, the use of pins neutralizes bending forces but not rotational or compressive forces. In contrast, Rush pinning and cross-pinning techniques are effective in neutralizing the forces acting on the physis, and are frequently used for the fixation of fractures in this region. Complications, often associated with poor reduction and alignment, can result in varus or valgus deviation and are associated with a high risk of implant failure or migration, malunion, and patellar luxation. It was concluded that the combination of Rush pins and an intramedullary pin resulted in adequate stabilization of the Salter Harris type I fracture of the distal femur in this rabbit.
Keywords: Orthopedic implants; osteosynthesis; trauma; bone repairing; lagomorph